2022
DOI: 10.4314/tjpr.v20i5.12
|View full text |Cite
|
Sign up to set email alerts
|

Delicaflavone induces apoptosis and autophagy, and improves the cytotoxicity of multiple myeloma cells to cisplatin by inactivating the AKT/mTOR pathway

Abstract: Purpose: To determine the effects of delicaflavone in multiple myeloma cells. Methods: Multiple myeloma cells were incubated with different concentrations of delicaflavone (20, 40, and 80 μM) or coincubated with 40 μM delicaflavone and 20 μM cisplatin. Cell viability and proliferation were investigated using MTT and colony formation assays, respectively. Flow cytometry and western blot analysis were applied to investigate cell apoptosis and autophagy. Results: Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It plays a role as the central regulatory point in the process of tumor cell differentiation, growth, and proliferation. Rapamycin specifically binds to the mTOR protein to effectively block the cell mTOR function, and also has an anti-tumor biological effect [11][12][13]. Studies have shown that ap2357, a derivative of rapamycin, can have a good effect on soft tissue tumors and malignant bone tumors, and inhibits the proliferation of sarcoma cells in intimal cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role as the central regulatory point in the process of tumor cell differentiation, growth, and proliferation. Rapamycin specifically binds to the mTOR protein to effectively block the cell mTOR function, and also has an anti-tumor biological effect [11][12][13]. Studies have shown that ap2357, a derivative of rapamycin, can have a good effect on soft tissue tumors and malignant bone tumors, and inhibits the proliferation of sarcoma cells in intimal cells in vitro.…”
Section: Discussionmentioning
confidence: 99%